COTTON SEED CARRIER SCREW CONVEYOR CONSTRUCTION IMPROVEMENT (American Journal of Interdisciplinary Research and Development, 2024)
Through this work, great attention is being paid to the creation of effective raw material processing technologies and equipment and their introduction into production. In this direction, it has been shown that the creation of adaptive automated systems for the implementation of raw material processing technology, the development of new methods and directions of processing technology, and the implementation of targeted scientific research are important tasks.